Chemical characterization and analysis of CMS biofertilizer and its application in vegetable farming - Mohd Rawa, Ispal (Universiti Malaysia Sarawak (UNIMAS), 2012)
Few decades ago farmers have adopted the strategy of increasing crop yields by applying compost for supplying nutrition to crops. The compost is consist of a large population of a specific group of beneficial microorganisms for enhancing productivity of soil and maintains soil fertility. The purpose of this study was focusing on the chemical characterization and analysis of the compost produced by CMS Agrotech Sdn. Bhd. to ensure that the compost produced is achieving the standard quality for marketing. Investigation carried out involves chemical analysis of heavy metals in compost, water holding capacity, moisture content, pH determination, porosity, microbial succession and nutrient content viability. The percentage carbon and nitrogen content is determined to know the exact carbon to nitrogen ratio (C:N ratio). In addition, plant seed germination test and potting trial were also conducted to determine and evaluate the performance of the compost produced towards promoting the growth of the plant. Generally, all compost samples were analyzed in this study was performed high quality and are recommended use for soil fertilizer. The compost samples possess optimum pH, moisture content, porosity, water holding capacity, low heavy metal contents and contained adequate amount of nutrients. However, the compost samples were low in the C:N ratio and the microbial analysis of compost samples was not according to the standard quality for composting (BSI PAS 100).